Tracing the status of silica fume in cementitious materials with Raman microscope. (20th January 2018) - Yue, Yanfei; Wang, Jing Jing; Bai, Yun
Highlights: Raman microscope can trace the status of silica fume (SF) in cementitious materials. The agglomerates exist both in the raw SF slurry and the hydrated SF-PC pastes. Abstract: Silica fume (SF) is an essential material for formulating high performance concrete (HPC). However, its small particle size could cause safety-hazards. Although replacing SF powder with slurry can somehow avoid the potential bio-toxicity, its long-term stability within cementitious materials is unknown. In this study, Raman microscope which combines Raman spectroscopy with light-optical microscope was successfully applied to characterise the composition and morphology of SF in original slurry and hydrated SF-Portland cement (PC) pastes. The unhydrated SF-agglomerates were clearly detected in the original SF slurry and the 22-hour and 6-month hydrated SF-PC pastes.